GREEN ACCOUNTING PADA LOCAL CHAIN MANAGEMENT HOTEL DAN INTERNATIONAL CHAIN MANAGEMENT HOTEL DI BALI - Tri Budi Artani ketut (Universitas Airlangga, 2019)
This study aims at identifying whether local chain management hotel and international chain management hotel in Bali have different environmental awareness, environmental responsibility, environmental involvement, environmental accounting reporting, as well as environmental audit. The data used in this study is primary data, which were collected by using instrument that was adapted from Susilo (2008). There are 45 questionnaires that meet the requirements for testing. The results of the Independent Sample T-test analysis show that there is no difference of environmental awareness between local chain management hotel and international chain management hotel in Bali. However, there are differences of environmental responsibility, involvement in protecting the environment, environmental accounting reporting as well as environmental audit between local chain management hotel and international chain management hotel. This study provides an understanding of whether there are differences of the application of green accounting in local hotel chain management and international chain management hotel, something that, to the best of our knowledge, have never been investigated previously, especially in the hospitality business in Indonesia.